Pretendentes e profecias ou a experiência da indeterminação na Odisseia - Gustavo Henrique Montes Frade (2017)
The experience of uncertainty is one of the basic features of the representation of human characters and, consequently, of the suitors characterization throughout the Odyssey. This is demonstrated after initial remarks on divination, on Greek religious thought, on Homeric Studies (including the Homeric Question and the recognition of Homers oral traditional style), on poetry and on narrative. The suitors are characterized as reckless men who despise limits, who poorly evaluate their situation and misread the warnings they receive. The possibility of misreading signs helps maintain some uncertainty in the future, from the human perspective, as the skill of interpreting and correctly reacting to signs is a quality that distinguishes heroes from antagonists. The suitors, however, are individualized as moral agents and are represented in a more refined way than merely as pure collective evil. Their general punishment (in accordance with the gods will) becomes a relevant question to which the poem will give its extreme answer. When Athena appears as a man, she ends up revealing significant marks of human and divine communication. Her strategy of disguise is to deliver information only in a partial way, simulating human limitations of knowledge and ignoring her capacity of direct and effective action over the events (a resource that allows her to test mortals). The bird flight interpretation scenes, performed by Halitherses, Helen, Theoclymenus and Amphinomus (scenes analyzed with special attention in this work), show in different ways how humans may react to the divine indications (confirmed by the narrator or inferred by the characters). The gods are interested in human affairs and provide guidance; between the sign and the comprehension, though (between more or less veiled suggestions and actions), there is always an open space filled by the experience of uncertainty and indetermination. In Ithaka, the signs and their interpretations are indicators that the power of Odysseus house is in accordance with the will of the gods, a divine legitimation of the restored aristocratic social order. A sequence of signs will prepare the listener or reader for the final revenge.